The Influence of Leadership Style and Motivation on Employee Performance - Rigan Ahmad Sabastian (Almana : Jurnal Manajemen dan Bisnis, 2021)
Human resources are the main element that quality must be maintained in a company, good human resources are assessed based on the results of the performance of its employees. Leadership style and motivation are part of the factors that can affect the level of employee performance. This study aims to determine how much influence of leadership style and motivation on employee performance in the management services division of PT. Adyawinsa telecommunication & electrical Bandung either partially or simultaneously. This research is a descriptive quantitative method using primary and secondary data sources in the form of a questionnaire with 25 employees as respondents. The type of analysis used is path analysis, and to perform data processing, the author uses the help of the SPSS version 23 program. not good, and also the employee's performance is in a bad category. And then the results of this study indicate that partially and simultaneously leadership style has a direct effect on employee performance, then motivation has a direct effect on employee performance and leadership style and motivation affect employee performance.